Calculation methods of RF power requirement on an RF dee cavity of cyclotron - Silakhuddin Silakhuddin; Rian Suryo Darmawan; Agus Dwiatmaja; Ahsani Hafizhu Shali; Idrus Abdul Kudus; Taufik Taufik (Institute of Advanced Engineering and Science, 2023)
A calculation of the radio frequency radiofrequency (RF) power required to operate the RF dee cavity of cyclotron which of the two dee is in phase has been carried. In this calculation, the object is the RF dee cavity of the DECY-13 cyclotron which operates with an RF frequency of 77.77 MHz and a peak RF dee voltage of 40 kV. The power requirement was determined by calculating the dissipated power in the RF dee that was calculated by two methods. The first method using a relationship between the quality factor and lost power has resulted in the power requirement of 20.55 kW. The second method using a relationship between the electrical current and the lost power has resulted in the power requirement of 19.74 kW. The two results do not seem to have any significant difference. By these calculations, it can be determined the predicted power requirement for operating the RF dee of DECY-13 cyclotron was around 20 kW.